STUDI OPTIMASI POMPA DISTRIBUSI SPAM KOTA PALANGKA RAYA UNTUK EFISIENSI ENERGI - Alhamidiy, Abdillah Nur; Masduqi, Ali; Bustami, Bustami; Adhi, Bagas Wahyu (Jurnal Teknik Sipil Giratory UPGRIS, 2024)
SPAM of Palangka Raya City has a distribution unit which is powered by six pumps but only two pumps are functioning due to frequent damage to the pumps. The pumps that function is Pump III and Pump V. This research aims to evaluate pump efficiency and specific energy consumption (SEC) so that technical recommendations for optimizing existing distribution pumps are known. Pump III is installed with a VSD with a SEC value of 0.14 KWh/m3 with a pump efficiency of 70.41% so it does not require minor or major repairs but requires a new backup pump because it works 24 hours while Pump V has a SEC of 0.27 KWh/m3 with a pump efficiency of only 36.97% which requires a new pump replacement. Both pumps experienced the same problem, namely V-Unbalanced which reached 2.72-2.73%, causing a decrease in motor performance which could cause damage to the pump components and VSD, so a capacitor bank and voltage stabilizer were needed. The evaluation of energy loss in the distribution network was carried out by increasing the diameter of 57 pipe segments to reduce headloss to less than 10 m/km.